If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 3 + 8x Solving 6x = 3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6x + -8x = 3 + 8x + -8x Combine like terms: 6x + -8x = -2x -2x = 3 + 8x + -8x Combine like terms: 8x + -8x = 0 -2x = 3 + 0 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5
| 3/4= | | 3/10= | | 1+x^2=9 | | x^2+3x=-5x+4 | | -3x+5=8-2x | | 1-16y^4= | | 5c-7=8c-4 | | 15=-7-m | | x-4=3x+24 | | 0.8x+6.2=0.2x-1.0 | | n+8=3n | | x+7=6x+4-x | | -12q=84 | | 40+40*1= | | 4+16-(-1)= | | 3(2x-3)=4x+5 | | 7n=19 | | 5x-72=28 | | 8.2=2.6+8x | | 6x-2.5=1.1 | | 10(-1.4)-12=0 | | x+-1=-8 | | 5n^2-13n=28 | | 3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3-3= | | 2+5(x-3)=2(2x+1) | | 17=k+1 | | 7x+3.4=-1.5 | | p(5)=10x-7 | | -2x-12=7-3x | | X+6=x^3 | | 5(2x+4)-3(x+2)= | | 18+11x=23 |